ENHANCING THE LONGEVITY OF THE CYMBIDIUM HYBRID ‘PINE CLASH MOON VENUS’ THROUGH CHEMICAL APPROACHES - T. USHA BHARATHI; D. BARMAN (The Bioscan, 2015)
An investigation was carried out to study the role of sucrose, antimicrobial and anti ethylene agents in the form of pulsing treatment on post harvest keeping quality of Cymbidium orchid hybrid ‘Pine Clash Moon Venus. The cut spikes were subjected to two hours of pulsing with 5% sucrose, 8% sucrose, 10% sucrose, 8-HQS 200 ppm, 10% sucrose + 8-HQS 200 ppm, 10% sucrose + 8-HQS 200 ppm + BA 50 ppm, 0.5mM STS and distilled water as control. Significant differences were recorded among different treatments for fresh weight increase, water loss, water uptake, physiological loss in weight per cent, vase life, appearance of the flower and rostellum colouration. The results revealed that, among the various pulsing solutions used, two hours pulsing with 5% sucrose recorded highest increase in fresh weight on 3rd day (2.33 gm) as compared to control (0.61g). Total water uptake was maximum in 8% sucrose (38.95g) followed by 5% sucrose (31.99g) and total water loss was maximum in 8% sucrose (40.00g). Vase life of flower was highest in 5 % sucrose (56 days) followed by 8% sucrose (54.78 days). The present study revealed the effect of pulsing with different chemicals on the post harvest life of Cymbidium orchid hybrid ‘Pine Clash Moon Venus’ and generate the flowers with longer vase life.